Results of an International Survey for Risk Assessment of Honey Bee Health Concerning Varroa Management - Alessandra De Carolis; Adam J. Newmark; Jieun Kim; Joseph Cazier; Ed Hassler; Marco Pietropaoli; Chris Robinette; Giovanni Formato; Junxia Song (Applied Sciences, 2022)
Here, we present the results of an online international survey concerning the adoption of good beekeeping practices and proper biosecurity measures for the management of varroosis in Apis mellifera. The survey was designed as a risk assessment tool by the Food and Agriculture Organization of the United Nations (FAO), the International Federation of Beekeepers’ Association (Apimondia), the Center for Analytics Research & Education (CARE) at Appalachian State University, and Istituto Zooprofilattico Sperimentale Lazio e Toscana (IZSLT). The data collected investigated the beekeeping techniques, treatments, and training beekeepers adopt concerning the varroa mite. The idea was to validate a tool able to collect and compare, in the different areas of the world, the management measures adopted by beekeepers to face this major parasitic disease of honey bees. The survey was disseminated online for a period of 14 months (January 2019–March 2020) through the FAO website. A total of 861 responses were received, most of them from the Americas (20.9%) and Europe (74.7%). Concerning the control measures useful in combating varroa, the results showed an overall awareness of the usefulness of biosecurity measures in beekeeping (BMBs), which we compare across regions. The majority of the beekeepers (89.9% in the Americas and 82.8% in Europe) were interested in additional bee health training and, at the same time, were willing to connect themselves with veterinary experts specialized in bees. This is an indication that beekeepers recognize the importance of training and experts’ advice. This study revealed the efficacy of the survey adopted as a useful assessment tool that will be further disseminated, even in geographic regions heretofore not investigated, to provide useful information on the status of the beekeeping sector.